Pb2+ recovery from real water samples by adsorption onto nano Fe3O4/chitosan‐acrylamide hydrogel ions in real water samples - Arman Samadzadeh Mamaghani; Mohammadreza Manafi; Mohammad Hojjati (IET Nanobiotechnology)
Abstract This study examined the removal of Pb(II) using magnetic chitosan hydrogel adsorbent from diverse sample waters. Spectrometry was used to track the effects of magnetic acrylamide nanocomposite dose, pH extraction, and contact duration on Pb(II) removal from sample water. This research also looked at adsorption isotherm models for the sorption of Pb(II). The magnetic chitosan hydrogel adsorbent Pb(II) adsorption capability was 31.74 mg/g respectively. The Freundlich isotherm model fits the removal of Pb(II) utilising magnetic chitosan hydrogel adsorbent. In addition, this adsorbent was shown to have a qmax value of 31.74 mg/g of Pb2+ ions, which is considered to be of high efficiency for Pb2+ ion removal. The studied kinetic models have determined that the pseudo‐second‐order linear model is more suitable to explain the adsorption of lead (II) on magnetic chitosan hydrogel adsorbent. Also, chemical adsorption is the rate‐limiting step in the adsorption process of lead (II) ions.